Elevated circulating sclerostin correlates with advanced disease features and abnormal bone remodeling in symptomatic myeloma: Reduction post-bortezomib monotherapy - Terpos, E.; Christoulas, D.; Katodritou, E.; Bratengeier, C.; Gkotzamanidou, M.; Michalis, E.; Delimpasi, S.; Pouli, A.; Meletis, J.; Kastritis, E.; Zervas, K.; Dimopoulos, M.A. (International Journal of Cancer, 2012)
Sclerostin is a Wingless and Int-1 inhibitor, which is produced by osteocytes and inhibits osteoblast-driven bone formation. Sclerostin is implicated in the pathogenesis of bone loss in metabolic bone disorders but there is no information for its effect on multiple myeloma (MM)-related osteolytic disease. We evaluated circulating sclerostin in 157 newly diagnosed patients with symptomatic myeloma, in 25 with relapsed myeloma who received bortezomib monotherapy, in 21 patients with monoclonal gammopathy of undetermined significance (MGUS), and in 21 healthy controls. Patients with active myeloma had elevated circulating sclerostin compared to MGUS patients and controls (p < 0.01). MM patients who presented with fractures at diagnosis (n = 34) had very high levels of circulating sclerostin compared with all others (p < 0.01), whereas sclerostin correlated negatively with bone specific alkaline phosphatase (a bone formation marker; r = -0.541, p < 0.0001) and positively with C-telopeptide of collagen type-1 (a bone resorption marker; r = 0.524, p < 0.0001). Patients with International Staging System (ISS)-3 disease had higher circulating sclerostin compared to ISS-1 and ISS-2 MM (p = 0.001). Furthermore, patients with high sclerostin (upper quartile, n = 40) had a median survival of 27 months versus 98 months of all others (p = 0.031). Relapsed MM patients had higher levels of circulating sclerostin even compared to newly diagnosed patients (p < 0.01). Bortezomib monotherapy resulted in a reduction of sclerostin by almost 50% in both responders and non-responders. These results suggest that patients with active myeloma have elevated circulating sclerostin, which correlated with advanced disease features including severe bone disease. Our study indicates sclerostin as a possible target for the development of novel therapies to enhance osteoblast function in myeloma. Copyright © 2011 UICC.
Keywords: Bone disease; bortezomib; Dickkopf-1; multiple myeloma; osteoblast; osteocyte; Sclerostin